Morphological and Biochemical Alterations of Paddy Rice in Response to Stress Caused by Herbicides and Total Plant Submersion - MARCHEZAN,M.G. (2017)
ABSTRACT Herbicide selectivity in paddy rice varies in several aspects, among which are the environmental conditions. The aim of the study was to evaluate the effect of herbicide application and total plant submersion on morphological and biochemical changes in paddy rice. Total chlorophyll and carotenoids, catalase activity, ascorbate peroxidase and superoxide dismutase, total phenolic content, lipid peroxidation and hydrogen peroxide levels were assessed. Leaf samples were collected 24 hours and 7 days after the application of water regimes. The results observed in the first experiment show that cultivars Puitá INTA CL, IRGA 417 and IRGA 422 CL are more tolerant to total submersion. The most sensitive cultivars are IRGA 424, BRS Querência, EPAGRI 108 and BRS Taim. In general, cultivar Puitá INTA CL had lower oxidative damage than BRS Querência when under submersion. To eliminate excess free radicals, BRS Querência had increased activity of superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) than Puitá INTA CL under submersion. Formulations with imazethapyr + imazapic and imazapyr + imazapic caused greater reduction in the total chlorophyll and carotenoid contents at 7 days after the establisment of water regimes (DAT). Therefore, the data show that exposing cultivars to total submersion and herbicides increased oxidative stress as well as induced changes in the activities of antioxidant enzymes.